Improving the quality of the wifi MIMO communication channel based on dual polarization antennas - Ikeza Obasi A. D. (ХНУРЕ, 2020)
This paper work provides the basics of MIMO technology, standard of configuration, Antenna polarization choices, benefits of communication channel. Types of channels and the dual polarization Antenna for MIMO and how the dual polarization signal improves the communication quality.